Bidirectional Locomotion of Soft Inchworm Crawler Using Dynamic Gaits - Du, Liang; Ma, Shugen; Tokuda, Keisuke; Tian, Yang; Li, Longchuan (Frontiers in Robotics and AI, 2022)
Inchworm-styled locomotion is one of the simplest gaits for mobile robots, which enables easy actuation, effective movement, and strong adaptation in nature. However, an agile inchworm-like robot that realizes versatile locomotion usually requires effective friction force manipulation with complicated actuation structure and control algorithm. In this paper, we embody a friction force controller based on the deformation of robot-body, to realize a bidirectional locomotion. Two kinds of differential friction forces are integrated into a beam-like soft robot body, and along with the cyclical actuation of the robot body, two locomotion gaits with opposite locomotion directions can be generated and controlled by the deformation process of the robot body, i.e., the dynamic gaits. Based on these dynamic gaits, two kinds of locomotion control schemes, the amplitude-based control, and the frequency-based control, are proposed, analyzed, and validated with both theoretical simulations and prototype experiments. The soft inchworm crawler achieves versatile locomotion result via a simple system configuration and minimalist actuation input. This work is an example of using soft structure vibrations for challenging robotic tasks.